Factors affecting members’ participation in primary Dairy cooperatives in North Gondar zone of Amhara Region, Ethiopia - Nachimuthu, Dr.Kavitha; Derso, Beyene (International Journal of Scientific Research and Management (IJSRM), 2018)
Dairy co-operatives can improve access to market information, reduce costs and price risks of marketing and can increase producers’ access to technology, extension and related services and enhance bargaining power of dairy producers. The overall objective of the society is to alleviate members’ milk marketing problem and increase their income generated from the milk and milk by products.. So, this paper will find out the solution for those problems. The major objective of this study is to identify factors affecting members Participation in primary cooperatives in north Gondar zone. North Gondar Administrative Zone and in the zone 8 districts and 11 primary dairy cooperatives were selected purposively and 114 sample respondents were selected by using simple random sampling methods. Both qualitative and quantitative data as well as primary and secondary data were used in the study.. The result of the study indicated that except access to transport, feed availability and proximity all discrete and continuous variables had a significant association with members’ participation of the dairy cooperatives. The binary logistic regression result of members’ participation also shows that from the hypothesized thirteen independent variables only six variables were found to be significantly influenced members’ participation of primary dairy cooperatives. As a recommendation, the concerned bodies, members and dairy cooperatives should give emphasis on factors like transport access, number of milking cows, price of raw milk, training access, patronage dividend and access of credit to increase members’ participation in GA meeting, decision making, election and economic activities of dairy cooperatives.